Transforming Green HRM Research for Environmental Sustainability : A Comprehensive Analysis of Theoretical Underpinnings and Nomological Network in the Service Sector - Maheshwari, Aman; Buddhapriya, Sanghamitra; `Soni, Tarun K.; Pareek, Ankita (Indian Journal of Marketing, 2026)
Purpose : The paper examined the empirical studies on green human resource management in the service sector and focused on identifying the theoretical underpinnings and nomological networks in those studies. Methodology : Using data from Web of Science, Scopus, and Google Scholar, the study examined empirical papers on Green HRM in the service sector between 2011 and 2024. Findings : We concluded that theoretical frameworks from psychological and social psychological disciplines dominated the existing studies. The nomological network analysis highlighted the use of Green HRM variables at individual and organizational levels, particularly as mediators or moderators. Practical Implications : The findings highlighted the importance of integrating Green HRM practices with team-level dynamics and cross-disciplinary approaches to enhance sustainability efforts. Originality : This paper summarized the Green HRM literature and proposed new directions for research.